A novel mutation within a transmembrane helix of the bile salt export pump (BSEP, ABCB11) with delayed development of cirrhosis. (12th June 2013) - Stindt, Jan; Ellinger, Philipp; Weissenberger, Katrin; Dröge, Carola; Herebian, Diran; Mayatepek, Ertan; Homey, Bernhard; Braun, Stephan; Schulte am Esch, Jan; Horacek, Michael; Canbay, Ali; Schmitt, Lutz; et al.
Abstract Background & Aims The bile salt export pump (BSEP, ABCB11) is essential for bile salt secretion at the canalicular membrane of liver cells. Clinical phenotypes associated with BSEP mutations are commonly categorized as benign recurrent intrahepatic cholestasis (BRIC‐2) or progressive familial intrahepatic cholestasis (PFIC‐2). Methods The molecular basis of BSEP‐associated liver disease in a sibling pair was characterized by immunostaining, gene sequencing, bile salt analysis and recombinant expression in mammalian cells and yeast for localization and in vitro activity studies respectively. Results Benign recurrent intrahepatic cholestasis was considered in a brother and sister who both suffered from intermittent cholestasis since childhood. Gene sequencing of ABCB11 identified the novel missense mutation p.G374S, which is localized in the putative sixth transmembrane helix of BSEP. Liver fibrosis was present in the brother at the age of 18 with progression to cirrhosis within 3 years. Immunofluorescence of liver tissue showed clear canalicular BSEP expression; however, biliary concentration of bile salts was drastically reduced. In line with these in vivo findings, HEK293 cells showed regular membrane targeting of human BSEPG374S, whereas in vitro transport measurements revealed a strongly reduced transport activity. Conclusions The novel mutation p.G374S impairs transport function without disabling membrane localization of BSEP. While all other known BSEP mutations within transmembrane helices are associated with PFIC‐2, the new p.G374S mutation causes a transitional phenotype between BRIC‐2 and PFIC‐2.